Associations between biological age acceleration and hospitalization burden of community-acquired pneumonia: a cohort study - Wang, Biying; Qian, Chen; Yi, Liping; Zhang, Youyi; Yu, Hongjie; Liu, Xiaohua; Jiang, Yonggen; Zhang, Tao; Zhao, Genming (GeroScience, 2025)
Community-acquired pneumonia (CAP) is a leading infectious cause of death, particularly in the elderly. Although biological age (BA) acceleration is a major risk factor for age-related diseases, its role in infectious diseases such as CAP remains unclear. This study investigated the association between BA acceleration and CAP hospitalization and mortality. We analyzed data from 47,181 participants in the Shanghai Suburban Adult Cohort and Biobank. BA was estimated using the Klemera-Doubal (KDMAge), Phenotypic age (PhenoAge), and homeostatic dysregulation (HD) methods, with validation of the customized BA algorithms. BA acceleration was calculated as residuals from regressing BA on chronological age. We performed time-dependent Cox regression (Andersen-Gill model) to assess associations with CAP outcomes, and generalized linear models to evaluate length of stay (LOS). The average KDMAge acceleration, PhenoAge acceleration, and log(HDAge) at baseline were 1.29 ± 5.80, -0.94 ± 4.28, and 4.18 ± 0.01 years, respectively. Each 1 standard deviation (SD) increase in KDMAge acceleration was associated with a 7% (95% CI: 1, 15%) higher CAP hospitalization risk and a 56% (95% CI: 23, 97%) higher risk of CAP-related mortality. Similar associations were observed for PhenoAge and log(HDAge). Prolonged LOS was associated with PhenoAge acceleration and log(HDAge). Risks were especially elevated among those aged ≥ 60 and males, with greater susceptibility at equivalent BA acceleration levels. Accelerated BA is associated with CAP hospitalization and related deaths, especially among males and the elderly. These findings suggest that BA may help identify individuals at higher CAP risk, offering potential for early intervention.